Recruitment process and the performance of Tanzania Petroleum Development Corporation, - Naburi, Elinaike Geofrey (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University Dar es Salaam College Campus in partial fulfillment of the requirements for the award of the degree of Masters of Science in Human Resource Management (MSc-HRM) of Mzumbe University.